Partnerships to Address Obesity Disparities in Hawai`i: The PILI `Ohana Project - Nacapoy, Andrea H. (2008)
Community-based participatory research (CBPR) is an approach to scientific research that is gaining broader application to address persistent problems in health care disparities and other hypothesis-driven research. However, information on how to form CBPR community-academic partnerships and how to best involve community partners in scientific research is not well-defined. The purpose of this paper is to share the experience of the Partnership for Improving Lifestyle Interventions (PILI) `Ohana Project in forming a co-equal CBPR community-academic partnership that involved 5 different community partners in a scientific research study to address obesity disparities in Native Hawaiians and other Pacific Peoples (i.e., Samoans, Chuukese, and Filipinos). Specifically, the paper discusses 1) the formation of our community-academic partnership including identification of the research topic; 2) the development of the CBPR infrastructure to foster a sustainable co-equal research environment; and 3) the collaboration in designing a community-based and community-led intervention. The paper concludes with a brief summary of the authors' thoughts about CBPR partnerships from both the academic and community perspectives.